Historia y filosofía: Perspectiva Hegeliana. (2021)
In the article “Annotations about the Hegelian System: Idea, unfolding and freedom” (Muñoz, 2003) we have made one first approach to the System of Hegel, trying more than to show it in a scheme or sketch, to present it, in the first place, as the unfolding of the Idea, fundamental element of all his philosophy and, in second place, to show how such unfolding is not finished as it has been tried to present by some authors, but it is in constant movement, unfinished speculation in search of the Human Freedom. In this opportunity we used these instruments to aproach to another disturbing and inescapable problem in his philosophy and, that occupies the unfolding of the Idea: the history. The reader will find in this writing, like in the referred one about the Hegel system, that the Hegelian consideration about the history is not presented in an expositive may; what is interesting for us here, more than a detailed exposition, that may be in the history texts of phylosophy, is to aproach to some problems referred to the Hegel system about the theme and next, present and approach to his conception of history. All the article tries to show the relevance that this system keeps with the problem that we are dealing with, and the importance of the human fredom as the main idea of the phylosophy of Hegel. Although we have tried to act with all the rigor in the use of the sources, this article -like to the one presented in the previous issue- is written as an essay, so, it is assumed like an open reflection and therefore it is subdued to critic and correction